IMPLEMENTASI KEBIJAKAN TINDAK LANJUT HASIL PEMERIKSAAN KEUANGAN NEGARA DALAM PENYELENGGARAN JAMINAN KESEHATAN NASIONAL - Sri Haryati; Bahrullah Akbar; Khasan Effendy; Sampara Lukman (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2020)
The purpose of this study was to analyze the implementation of the follow-up policy on the results of the examination of state finances in the implementation of the National Health Insurance. Research uses a qualitative research approach. Data collection was carried out using interview, observation and documentation study techniques. Data analysis was performed descriptively with the observers' triangulation analysis. The results of the study found that the implementation of the follow-up results of the examination was not yet fully effective, because 5 of the 26 recommendations that had been followed up by the Health BPJS were not in accordance with the recommendations of the Supreme Audit Agency. The implementation of the policy on the follow up of the results of the state financial audit in the implementation of the National Health Insurance covers actions and improvements that include: (1) Establishment of adequate regulations related to testing the truth of BU PPU data; (2) Distribution of KIS which is still in the possession of the Health BPJS, and report its progress to the Ministry of Health and Ministry of Social Affairs in the context of coordinating participant addresses; (3) The head of the SDS and General groups carries out promotional activities through the media directly using the intended media; (4) Coordinating with the Regional Government regarding the integration of Jamkesda; (5) Determination of KPI that is able to realize financial independence; and (6) Coordinate with the Ministry of Social Affairs for inaccurate PBI data.